Developments in Primary Aldosteronism Subtyping Using Steroid Profiling - Wannachalee, Taweesak; Turcu, Adina F. (Hormone and Metabolic Research, 2020)
Adrenal venous sampling is the standard of care for identifying patients with unilateral primary aldosteronism, which is often caused by an aldosterone producing adenoma and can be cured with surgery. The numerous limitations of adrenal venous sampling, including its high cost, scarce availability, technical challenges, and lack of standardized protocols, have driven efforts to develop alternative, non-invasive tools for the diagnosis of aldosterone producing adenomas. Seminal discoveries regarding the pathogenesis of aldosterone producing adenomas made over the past decade have leveraged hypotheses-driven research of steroid phenotypes characteristic of various aldosterone producing adenomas. In parallel, the expanding availability of mass spectrometry has enabled the simultaneous quantitation of many steroids in single assays from small volume biosamples. Steroid profiling has contributed to our evolving understanding about the pathophysiology of primary aldosteronism and its subtypes. Herein, we review the current state of knowledge regarding the application of multi-steroid panels in assisting with primary aldosteronism subtyping.
Keywords: primary aldosteronism; adrenal vein sampling; steroids; adrenal; aldosterone